The Sale of Treasury Stocks and Protection of Management Rights - Sung Ick Cho (Korea Development Institute (KDI), 2017)
Treasury stocks play a vital role in retaining, protecting and transferring management rights in large enterprises. However, the sale of treasury stocks is essentially identical to the issuance of new shares in economic nature. Therefore, using treasury stocks to protect management rights could obscure the equal treatment of shareholders. Even if such practices are permitted for policy purposes, the government needs to put other measures into place to protect general and minority shareholders from the damages that may arise. - The sale of treasury stocks and the issuance of new shares are the same in economic nature since both increase stock trade volume and seek outside funding. - Within the legal system, the difference between the sale of treasury stocks and issuance of new shares seems to have been created intentionally during the legislative process. As a result, controlling shareholders are able to use treasury stocks to defend their management rights. - Although identical economic natures do not necessitate identical regulations, policy considerations can be rationalized if the positive economic impact from the protection of management rights, through the sale of treasury stocks, is significant. - It is often the case that having a single managing executive to control two companies is more economically efficient, in terms of business synergy and reduced transaction costs. - Affiliated companies that are mobilized to help the controlling shareholder protect his/her management rights could suffer from a loss in efficiency, for instance lost opportunities for better investments. - Unlike general and minority shareholders, because controlling shareholders take into account the control premium when deciding on the sale of treasury stocks, the gains are highly likely to be focused on them, creating losses for the others. - The controlling shareholders' decision to sell treasury shares to white knights could generate losses for general and minority shareholders since it is a 'rushed sale,' while the controlling shareholders reap the benefits of maintaining the control premium. - Selling treasury shares to affiliated companies is mostly aimed at strengthening management control by increasing the holding stake and restructuring the entire group. - If it is difficult to expect certain business synergies, the sale will not be welcomed by the purchasing company's general and minority shareholders. - In the mid- to long-run, the current laws and systems need to be revised so that the transaction of treasury stocks fits the economic nature. - Even if the current laws and systems are maintained, regulations that could generate losses for general and minority shareholders need to be overhauled as soon as possible.
Keywords: 330